Methods and measures of source monitoring in children: A scoping review. - Li, Qiuhong; Li, Mengyuan; Wu, Chao (British Journal of Developmental Psychology, 2025)
Source monitoring (SM) refers to attributing sources of information. There are various methods for measuring SM in children. We searched the PubMed, PsycINFO, Embase, Web of Science and Cochrane Library databases from their inception to February 24, 2023, to summarize the methods and measures of SM in children, identifying 141 studies. The procedure for the SM tasks encompassed encoding, interval and testing. The encoding tasks were classified into ground‐based activities (n = 67), computer‐based experiments (n = 42) and mixed methods (n = 34). The testing approaches were categorized into old/new recognition and source discrimination, n‐alternative forced‐choice, yes/no questions and recall/direct questions. Among 10 commonly used indicators, source‐correct, source‐incorrect, discrimination score and source accuracy were recommended to present the SM function. We also discussed the advantages and disadvantages of different SM methods in children, providing a reference for researchers to design and select SM measurements that meet their research objectives.